Penerapan Jurnal Belajar untuk Meningkatkan Keterampilan Bertanya Calon Guru IPA - Nurfitra Yanto; Ramlawati Ramlawati; St. Mutia Alfiyanti Muhiddin (Universitas Negeri Makassar, 2022)
This study aims to determine the increase in questioning skills of prospective science teacher students. This type of research is Classroom Action Research. This research was designed as a classroom action research which consisted of 2 cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. This research was carried out in the Science Education Study Program, FMIPA UNM and the subjects of this research were students of the Program Studi Pendidikan IPA who took the IPA Sekolah 1 course in the 2022/2023 academic year. The data in this study can be in the form of qualitative data. Qualitative data in the form of learning journals made by students. The learning journal contains material conclusions, interesting things related to the material being taught, questions asked, and temporary answers to questions asked. The questions contained in the study journal are classified based on the Cognitive level of Bloom's Taxonomy and are analyzed quantitatively. In cycle I, student questions were directly answered by the subject lecturer. The results obtained were that the number of students who asked questions C1 was 20, C2 was 51, C3 was 25, C4 was 3, and there were no questions with cognitive levels C5 and C6. In cycle II, the questions posed by students were discussed and discussed by the students themselves, the course lecturer only served as a facilitator, so the number of questions at the cognitive level C1 was 6, C2 was 53, C3 was 11, C4 was 17, C5 was 7. Based on From these results, it can be concluded that the questioning skills of prospective science teacher students have increased.